PENGARUH KOMPETENSI, LINGKUNGAN KERJA, DAN M OTIVASI KERJA TERHADAP KINERJA PERAWAT (Studi Kasus Pada RSUD AMBARAWA Kab. Semarang) - Declara Wardani, 11.05.51.0057 (Students Journal of Economic and Management, 2015)
This study aimed to examine the influence of competence, work environment, and motivation on employee performance. This study was conducted at Ambarawa Hospital, Semarang district.Sample method used purposive sampling with the criteria is nurses of Ambarawa Hospital, Semarang district and given permission to fill out a questionnaire. Number of sample taken are based on the opinion Uma Sekaran ( 2000) which states that an adequate sample size for the study was greater than 30 and less than 200. And the influence of the relationship between variables is described by using multiple regression analysis.Results showed that competence, work environment and work motivation have positive and significant influence on employee performance. So if competence, workÂ  environment and work motivation is getting better, the performance of employee generated will be better too. Key words; competence, work environment, motivation, and employee performance